2019
DOI: 10.1177/1557988319863542
|View full text |Cite
|
Sign up to set email alerts
|

HIV Testing Among Middle-Aged and Older Men Who Have Sex With Men (MSM): A Blind Spot?

Abstract: Middle-aged and older men who have sex with men (MSM) are one of the most underestimated populations with regard to HIV/AIDS infection, despite the worldwide trend of increasing prevalence in recent years. This population also has low rates of testing, although rare studies are done exclusively with middle-aged and older MSM assessing the factors associated with this prevalence. Thus, based on data from an exclusive online survey with middle-aged and older MSM who use geolocation-based dating applications, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 28 publications
0
22
0
2
Order By: Relevance
“…We were also struck by the fact that the data were collected during the period of the pandemic when the COVID-19 case curve in Brazil was on the rise and, as a result, there were a high number of new cases and deaths. However, the data revealed a scenario of continued sexual practices (casual, drug-using, unprotected, group sex) by MSM at levels similar to those recorded in studies slightly prior to the pandemic (21)(22)(23) , suggesting that this scenario may have worsened in subsequent months.…”
Section: Discussionmentioning
confidence: 63%
“…We were also struck by the fact that the data were collected during the period of the pandemic when the COVID-19 case curve in Brazil was on the rise and, as a result, there were a high number of new cases and deaths. However, the data revealed a scenario of continued sexual practices (casual, drug-using, unprotected, group sex) by MSM at levels similar to those recorded in studies slightly prior to the pandemic (21)(22)(23) , suggesting that this scenario may have worsened in subsequent months.…”
Section: Discussionmentioning
confidence: 63%
“…O fornecimento de informações sobre HIV é uma ação importante a ser realizada pelos serviços especializados, seja com parcerias heterossexuais, não heterossexuais, soroconcordantes ou discordantes. O empoderamento do usuário do serviço de saúde contribui para mudanças no quadro epidemiológico da atual situação global dessa infecção, principalmente para que se possa atingir a meta 90-90-90 estipulada pelo UNAIDS (3,10) .…”
Section: Discussionunclassified
“…O principal objetivo proposto pelo Programa Conjunto das Nações Unidas sobre HIV/Aids é que, até 2020, os países diagnostiquem 90% das pessoas com esse vírus, que 90% delas iniciem o tratamento precocemente, e 90% delas atinjam níveis de supressão, gerando uma redução na transmissão do HIV (3) .…”
Section: Introductionunclassified
“…A study focusing on the older MSM who use dating application has reported that the testing rate in older MSM was only 47%. 36 In the future, widely-covered HIV care and special program on older MSM should be promoted by the government and public health agencies to reach, educate, and help older MSM. Increasing the attention on older MSM is necessary in the implement of “90–90-90” AIDS ending plan.…”
Section: Discussionmentioning
confidence: 99%